High Expression of UPK3A Promotes the Progression of Gastric Cancer Cells by Inactivating p53 Pathway - Deliang Xu; Jing Guo; Hongwei Xu (Analytical Cellular Pathology)
Background. Gastric cancer is a common gastrointestinal tract cancer and is a considerable health burden worldwide. TCGA analysis found Uroplakin 3A (UPK3A) was upregulated in gastric cancer tissues. Our study was designed to investigate the underlying mechanism of Uroplakin 3A (UPK3A) in gastric cancer. Methods. Data from TCGA database were used to assess the expression, and Kaplan-Meier plotter analysis was used to assess the prognosis value of UPK3A. Furthermore, there are effects of UPK3A silencing on the activity, proliferation, migration, and invasion of human gastric cancer cells (SNU-216 and HGC-27) using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), colony formation, wound healing, and Transwell assays. In addition, the expression of UPK3A, p53, KLF4, ZMAT3, MDM2, and SP1 was detected by qRT-PCR and Western blot assay. Results. UPK3A was markedly upregulated in gastric cancer tissues compared to that in normal tissues, and patients with high UPK3A level showed poor prognosis. UPK3A was highly expressed in human gastric cancer cell lines compared to that in a normal human gastric epithelial cell line. Silencing of UPK3A inhibited the proliferation, migration, and invasion of gastric cancer cells. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed that UPK3A was involved in the p53 signaling pathway. UPK3A suppressed the activation of p53 signaling pathway, and treatment with Pifithrin-α (an inhibitor of the p53 signaling pathway) or silencing of p53 significantly reversed the effect of UPK3A silencing on the expression of p53, KLF4, ZMAT3, MDM2, and SP1. Conclusion. Our findings showed that UPK3A promotes the progression of gastric cancer by regulating the p53 signaling pathway and could be a potential therapeutic target for gastric cancer.